Competition between positive and negative allosteric effectors on muscarinic receptors - Proska, J; Tucek, S (Molecular pharmacology, 1995)
Alcuronium allosterically increases the affinity of cardiac muscarinic receptors for methyl-N-scopolamine (NMS), whereas gallamine has the opposite effect. We discovered that strychnine also increases the affinity of muscarinic receptors in rat heart atria for NMS. It is not known whether the positive and the negative allosteric effectors bind to the same binding site. To investigate this question, we elaborated on a theoretical model predicting changes in the binding of a classic radiolabeled ligand occurring in the presence of a positive and a negative allosteric effector that compete for the allosteric binding site. The model is based on data obtained at equilibrium and avoids uncertainties associated with the use of nonequilibrium methods for the evaluation of interactions between allosteric ligands. We examined changes in the binding of [3H]NMS to membranes of rat heart atria exposed to various concentrations of a positive allosteric effector (alcuronium or strychnine) and of a negative allosteric effector (gallamine) simultaneously. The binding data obtained were in perfect agreement with the model assuming competition between gallamine and alcuronium and gallamine and strychnine, strongly suggesting that these positive and negative allosteric effectors bind to identical or overlapping sites.
Keywords: Allosteric Site; kinetika; Rats; strychnin; Poisons; receptory muskarinové; skopolaminové deriváty; N-Methylscopolamine; triethojodid gallaminia; Scopolamine Derivatives; Tritium; tritium; Alcuronium; krysa rodu Rattus; Models, Biological; Receptors, Muscarinic; N-methylskopolamin; Animals; alkuronium; kompetitivní vazba; nikotinoví antagonisté; jedy; myokard; zvířata; Radioligand Assay; Myocardium; Binding, Competitive; Gallamine Triethiodide; Mathematical Computing; Kinetics; biologické modely; alosterické místo; radioligandová zkouška; Strychnine; Nicotinic Antagonists; matematické výpočty počítačové